The Relationship between Knowledge and Attitudes of Reproductive Organs Among Students - Rhousnaka, Dika; Putri, Helda Herdiani; Meilani, Lita Rizki; Aisy, Nada Rahadatul; Azhara, Putri Anissa (Yayasan Inspirasi El Burhani, 2025)
Background: Adolescence is a critical developmental phase involving physical and psychological changes, particularly in reproductive health. However, many adolescents lack adequate knowledge and hold negative attitudes due to limited education, cultural taboos, and discomfort discussing reproductive issues. These gaps may lead to poor hygiene practices and increased health risks. Objective: This study aims to analyze the relationship between students’ level of knowledge and their attitudes toward reproductive organ hygiene. Method: A cross-sectional study was conducted at SMPN 1 Ciamis between March 10–15, 2025, involving 33 female students. Data were collected using a structured questionnaire consisting of 25 true/false items for knowledge and 25 Likert-scale items for attitudes. Instrument validity was assessed using Pearson correlation, while reliability was tested using Cronbach’s Alpha (knowledge = 0.619; attitude = 0.514). Data were analyzed using descriptive statistics and Chi-square test (p < 0.05). Result: The majority of respondents had moderate to good knowledge of reproductive organ hygiene. However, the Chi-square analysis revealed no significant correlation between knowledge and attitudes (p = 0.897). Students with higher knowledge did not consistently show more positive attitudes. Conclusion: The findings indicate that knowledge alone is insufficient to shape students’ attitudes toward reproductive health. Educational programs should integrate emotional, cultural, and social components to effectively influence adolescent attitudes and behaviors. A comprehensive, participatory approach is essential to support healthier adolescent development.